Relationship between Leishmania IFAT Titer and Clinicopathological Manifestations (Clinical Score) in Dogs. (3rd June 2014) - Proverbio, Daniela; Spada, Eva; Bagnagatti de Giorgi, Giada; Perego, Roberta; Valena, Emanuela
Abstract : During canine leishmaniasis (CanL) due to Leishmania infantum, high levels of antibodies production are associated with the presence of various clinical signs, because of the deposition of soluble immune complexes in organs and tissues. The immunofluorescence antibody test (IFAT) is one of the most commonly used techniques for detection of anti- Leishmania antibodies. The purpose of this study was to assess whether there is a correlation between clinical signs and IFAT titers in dogs naturally infected with Leishmania . A retrospective study was performed on medical records of 49 dogs diagnosed with CanL. Information extracted from the medical records of each dog with CanL was clinical score, IFAT titer, serum total protein (TP), gamma globulin (IgG) and creatinine concentration, and protein creatinine ratio in urine sample (UP/UC) at each follow-up examination. Results show that dogs with highest IFAT titers recorded had higher mean clinical scores indicating a positive relationship (P < 0.0001 ) between anti- Leishmania antibodies (IgG) and clinical manifestations, which becomes more evident in severe clinical forms of canine leishmaniasis. Higher TP and IgG serum concentrations were recorded in dogs with higher clinical scores. Significant association was observed between UP/UC and the IFAT titer (P = 0.004 ).